Sensors and the City: Urban Challenges for Parking Occupancy Detection and Pricing. Issue 7 (December 2018) - Dey, Soumya S.; Dock, Stephanie; Pochowski, Alek; Sanders, Meredyth; Pérez, Benito O.; Darst, Matt; Sanchez, Eduardo Cardenas
Implementing performance parking using demand-driven hourly parking meter rates and real-time occupancy information improves the customer experience and provides more available on-street parking in selected cities across the United States. The implementation of performance parking is not necessarily simple, however, and planners must overcome a host of challenges posed by the urban environment. This paper discusses an approach with the potential to become the state-of-the-practice for developing real-time availability for on-street parking in an urban environment, including how the District Department of Transportation in Washington, D.C., dealt with challenges related to: sensor communication, on-street activity, special events, limited space, broader mobility issues, parking users, coordinating installation, and interagency coordination. Using lessons learned from this project, jurisdictions will be better prepared to deal with their own unique urban challenges, positioning themselves to capture real-time availability and implement performance-based pricing.